경기 북부 내 직거래 농산물의 잔류농약 실태조사 및 위해성 평가 - 임정화; 박포현; 임부건; 유경신; 강민성; 송서현; 강남희; 유나영; 김정은; 강충원; 김윤호; 서정화; et al. (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2020)
In this study, we investigated pesticide residues in 207 agricultural products distributed by direct trade in the northern area of Gyeonggi Province. A total of 94 general agricultural products and 113 eco-friendly agricultural products collected from local grocers and cooperative stores were analyzed by multiresidue method for 263 pesticides using GC (gas chromatography)/ECD (electron capture detector), GC/NPD (nitrogen phosphorus detector), GC-MS/MS (tandem mass spectrometry), LC (liquid chromatography)/PDA (photodiode array detector), LC/FLD (fluorescence detector), LC-MS/MS. All samples showing pesticide residues were general agricultural products collected from local food stores. The pesticide residue levels of 14 samples (6.8%) were below the maximum residue limits (MRLs) and one of them (0.5%) exceeded the MRLs. Sixteen pesticides were detected from samples of the following produce items: spinach, young cabbage, perilla leaves, mallow, cucumber, chives and water dropwort. The safety of the detected pesticides was assessed by monitoring the daily intake estimate (EDI) and the daily intake allowance (ADI) based on the amount of pesticides detected. The ADI percentage range (the ratio of EDI to ADI) was 0.0134-61.6259% and there was no health risk connected with consuming agricultural products in which pesticide residues were detected. 경기 북부 내 직거래 매장에서 유통 되는 농산물 207건을 수거하여 잔류농약의 실태를 조사하였다. 로컬푸드와 소비자생활협동조합(생협) 매장을 대상으로 일반농산물 94건, 친환경농산물 113건의 다소비 채소류를 수거하여 다종농약다성분 분석법으로 GC/ECD, GC/NPD, GC-MS/MS, LC/PDA, LC/FLD, LC-MS/MS를 이용하여 263종의 농약을 분석하였다. 잔류농약이 검출된 검체는 모두 로컬푸드 매장에서 수거한 일반 농산물로 14건의(6.8%) 시료에서 잔류농약이 검출되었고, 그 중 1건에서(0.5%) 잔류농약허용기준을 초과하였다. 총 16개 농약성분이 검출되었고 검출된 작물은 시금치, 얼갈이, 깻잎, 아욱, 오이, 부추, 미나리였다. 농약 검출량을 바탕으로 일일섭취추정량(EDI)과 일일섭취허용량(ADI)을 이용하여 위해성 평가를 하였으며, %ADI 값의 범위는 0.0134-61.6259%로 안전한 수준이었다.